Distribuição COM-Poisson na análise de dados de experimentos de quimioprevenção do câncer em animais - Ribeiro, Angélica Maria Tortola (2012)
Experiments involving chemical induction of carcinogens in animals are common in the biological area. Interest in these experiments is, in general, evaluating the chemopreventive effect of a substance in the destruction of damaged cells. In this type of study, two variables of interest are the number of induced tumors and their development times. We explored the use of statistical model proposed by Kokoska (1987) for the analysis of experimental data of chemoprevention of cancer in animals. We flexibility the Kokoska s model, subsequently used by Freedman (1993), whereas for the variable number of tumors induced Conway-Maxwell Poisson (COM-Poisson) distribution. This distribution has demonstrated efficiency due to its great flexibility, when compared to other discrete distributions to accommodate problems related to sub-dispersion and super-dispersion often found in count data. The purpose of this paper is to adapt the theory of long-term destructive model (Rodrigues et al., 2011) for experiments chemoprevention of cancer in animals, in order to evaluate the effectiveness of cancer treatments. Unlike the proposed Rodrigues et al. (2011), we formulate a model for the variable number of detected malignant tumors per animal, assuming that the probability of detection is no longer constant, but dependent on the time step. This is an extremely important approach to cancer chemoprevention experiments, because it makes the analysis more realistic and accurate. We conducted a simulation study, in order to evaluate the efficiency of the proposed model and to verify the asymptotic properties of maximum likelihood estimators. We also analyze a real data set presented in the article by Freedman (1993), to demonstrate the efficiency of the COM-Poisson model compared to results obtained by him with the Poisson and Negative Binomial distributions.